Synthesis of Guerbet Amine-Oxide for Enhanced Oil Recovery - Changxin Shi; Zhiping Li; Hong Zhang; Yajuan Chen; Minglong Zhang; Meng He (Journal of Chemistry)
Guerbet amine-oxide was synthesized by using Guerbet acid, N,N′-diethyl-1,3-propanediamine and hydrogen peroxide. Its structure was confirmed by FT-IR spectra and mass spectra. The critical micelle concentration (CMC) and the interfacial tension between the crude oil and water were measured. The results showed that the CMC of the Guerbet amine-oxide is 2.14 × 10−5 mol/L and the interfacial tension could be lowered to ultralow levels. The core flood test showed that the surfactant and polymer binary system could increase oil recovery by 24.7% above the water flood.